Detecting and preventing unbalanced bidding in South African public sector construction - Tilese, Neliswa; Makhaga, Thendo; Mphahlele, Matjelele; Zungu, Zamageda (University of the Witwatersrand, Johannesburg, 2024)
Unbalanced bidding in public sector infrastructure projects is a key challenge, involving the manipulation of unit prices without adjusting the overall bid. Unbalanced bidding increases the client’s financial risks and the likelihood of project abandonment by the contractor. Existing literature provides guidelines for detecting and preventing bid price imbalances but inadequately addresses the practical implementation and efficacy of these approaches. This research aims to evaluate the practices for detecting and preventing unbalanced bidding in the South African public sector against existing formal models. This qualitative case study employs semi-structured interviews with quantity surveyors from public sector clients in Gauteng, South Africa. The purposive, non-probabilistic sampling targets professionals with relevant expertise. A thematic analysis of the interview data reveals insights into the awareness, consequences, and practices associated with unbalanced bidding in the South African public sector. The study findings highlight the need for strengthened governance and accountability, more robust strategies for detection of unbalanced bidding, and enhanced education of practitioners to promote fair competition and ethical practices in awarding projects.
This paper was presented at the Proceedings of the WABER SuDBE 2024 Conference, 30th – 31st July 2024, University of the Witwatersrand, Johannesburg, South Africa.
Keywords: Front-end loading; Public sector construction projects; Tendering; Unbalanced bidding; SDG-11: Sustainable cities and communities